THE EFFORTS TO IMPROVE ACTIVITY IN LEARNING MATHEMATICS THROUGH TEAMS GAMES TOURNAMENT LEARNING MODEL - Dyah Ayu Nur Faradilah Hadiyati; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2019)
Learning mathematics is still a lesson that is considered difficult for students. Student activity also seems to be lacking. This can be seen from some students who pay less attention to the teacher's lessons, and some students chat with their friends. Students also do not want to ask the teacher if they have difficulty learning or working on math problems. Sometimes students lack the confidence to ask questions or express their opinions. For this reason, students need an active attitude in solving problems during the learning process of mathematics. This study aims to improve students' mathematics learning activities. This study's subjects were the sixth-grade students of Junior High School (SMP) Muhammadiyah Ngemplak Sleman Regency, totaling 32 students consisting of 20 male students and 12 female students. This research aims to apply the team's games tournament (TGT) type learning model. Data collection techniques were carried out by observation and interview methods. The research instrument used observation sheets and interview sheets. The data analysis technique in this study used a qualitative descriptive. This study indicates that passing the TGT cooperative learning model can improve mathematics learning activities in VIIA students in the Middle Semester of SMP Muhammadiyah Ngemplak Sleman Regency 2018/2019. This is shown from the results of the observation sheet of student learning activities in mathematics learning, which has increased every Cycle, namely in Cycle I, indicators of student enthusiasm in participating in learning amounted to 59,38% with sufficient criteria, student and teacher interaction of 55,86% with sufficient criteria, the interaction between students was 53,52% with sufficient criteria, group collaboration was 62,90% with good criteria, student activity in the group was 57,82% with sufficient criteria, student participation in concluding the discussion result was 55,86% with sufficient criteria. While in Cycle II, each indicator has increased, namely the indicator of student enthusiasm in participating in learning amounting to 79,69% with good criteria, the interaction between students and teachers amounted to 73,83% with good criteria, the interaction between students was 71,10% with good criteria, group collaboration amounted to 78,91% with good criteria, student activities in the group amounted to 76,95% with good criteria, student participation in concluding the results of the discussion amounted to 73,44% with good criteria.